Concentrations of health-promoting phytochemicals in ripe mango fruit triggered by postharvest application of elicitors - Vithana, M.; Singh, Zora; Johnson, Stuart; Gupta, Ritu (John Wiley and Sons Inc., 2018)
BACKGROUND: Mango fruit harvested at green mature stage were treated with methyl jasmonate (MeJA), nitric oxide (NO), or salicylic acid (SA) to investigate their effects on phytochemical concentrations in ripe fruit. RESULTS: Fruit fumigated with MeJA showed the highest increase in the concentrations of gallic acid (33.0%), caffeic acid (80.0%), total phenols (38.4%), and total antioxidant capacity (20.9%) in the peel, and total carotenoids (48.7%) in the pulp, compared to control. The fruit dipped in SA showed the highest increase in the concentrations of lupeol (59.8%) and ferulic acid (73.2%) in the pulp and ferulic acid (67.4%) in the peel. Fruit fumigated with NO or MeJA showed the highest concentrations of lupeol in the peel (94.3%, 119.4%), and gallic acid (37.9%, 61.0%), total phenols (62.7%, 31.0%), and ascorbic acid (17.7%, 18.8%) in the pulp respectively. All the elicitor treatments were significantly effective in increasing concentrations of mangiferin and chlorogenic acid in the pulp and peel, vanillic acid in the peel, and total antioxidant capacity in the pulp. CONCLUSION: Overall, MeJA (10-5 to 10-4 mol L-1) was identified as the most effective elicitor for triggering phytochemical production during ripening of harvested mango fruit. © 2018 Society of Chemical Industry.